Coal Mining and Local Environment: A Study in Talcher Coalfield of India. Issue 10 (4th September 2017) - Mishra, Niharranjan; Das, Nabanita
Despite government's repeated assertions for the sustainable mining extraction and development of rural and tribal communities living near the vicinity of mining areas, these have not been converted into implementable solutions. The natural resources from rural and tribal areas are being exploited to meet the ever-increasing requirements and aspirations of the affluent groups. With the above background, this article, taking both experimental and control villages into account, tried to explore the impact of coal mining on local environment. Although dealing with local environment, it has mostly focused on sociological impact of mining in air, water, and noise pollution. The data collected show that the suspended particulate matter concentration is alarmingly high in few sampling locations, whereas respirable suspended particulate matter concentration which once used to be within acceptable limits is now gradually approaching its standard acceptable value of 300 µg/m 3 . Along with uncovered coal transportation, lack of water spraying system and movement of heavy vehicles have brought an addition to air pollution to the locality. The extraction of mining has influenced the water table. The data collected from State Pollution Control Board, Bhubaneswar, show that suspended sediments and chemical oxygen demand in most of the mining areas and biological oxygen demand in few cases have crossed the specific standard. Along with this, household survey was conducted by covering 6 villages and 600 households. The study was undertaken by following experimental design where 450 households were taken from experimental, ie, mining villages, and 150 households have been selected from nonmining areas. Of the 450 households, around 96.44% villagers responded that Mahanadi Coalfields Limited is not taking any mitigation measures to apprehend the pollution caused by mining operations.